Technical skills in the professional practice of engineering in Costa Rica: A neuro correlation analysis - Sánchez-Sánchez, Juan Diego (Uniciencia, 2022)
The study is aimed at defining the correlations and affectation that the demographic variables of gender, age, and educational level have in the technical skills for engineering. The paper analyzes crossover data of a field study applied to a random probability sample of active engineers in Costa Rica. The theoretical bases needed for understanding the neurobehavioral factors to approach a given technical skill are defined and analyzed in an applicative manner based on crossed results and linked to the demographic variables of interest in the study subjects. To conclude, the paper studies multiple statistical correlations in terms of skills and demographic elements of interest such as educational level and age. Worth mentioning are the direct influences that age and educational level have on technical skills, with average coefficients amounting to 5.01% and 3.45%, respectively. In addition, an opposite correlation is observed in terms of skills such as mathematics and programming. A relationship of interest is established, in which technical skills seem to be directly related to the independent variables.